Critical assessment of nursing profession in Saudi Arabia: With Reference to Work Environment - Anwar Ahmed Faqihi; Hufthyah Ibrahim Abdulrahman Assiry; Norah Omar Hassan Hukumi; Hind Saleh Alzahrani; Raghdah Essam Nojoom; Rehab Hamza Alhawsawi; Rakan Abdullah Almutairi; Samia alasmar owiada alruwili; Fatima Abdu Ahmad Mohammad; Waleed saada tallah albage; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Promoting nursing as a viable career path that many people can pursue is one of the Ministry of Health’s objectives; in order to achieve Vision 2030 in Saudi Arabia, a healthy practice environment is necessary to improve patient care and nurse retention rates. The World Health Organization claims that there is a global shortage of health professionals, with nurses and midwives making up over half of the need. This present study will evaluate the scenario with a primary data approach using a detailed questionnaire, which will be exercised with the selected set of nurses in hospitals of Makkah city.